Accounting Students' Perceptions of Ethics in Financial Statement Preparation (Study on Accounting Students at PTNs in East Java) - Sutri Handayani; Abdul Ghofur (Jurnal Mantik, 2021)
The perception of male and female accounting students regarding the ethics of preparing financial statements can be measured in 5 aspects. These basic aspects are: misstate, cost and benefit, disclosure, responsibility, and earnings management to users of financial statements. The purpose of this study is to analyze whether or not there are differences in the perceptions of male and female accounting students about the ethics of preparing financial statements. The population in this study were 273 accounting students at PTN in East Java in semester 6. The questionnaires were randomly distributed to a sample of 73 students with details of 28 male accounting students and 45 female accounting students. This research is a quantitative research because the data to be used in this study is primary data obtained through questionnaires. The analytical tools used include validity testing, reliability testing and hypothesis testing with independent sample t-test. The results of this study indicate that male accounting students have better perceptions than female accounting students. While the results of the Independent Sample t-test on disclosure, responsibility, and earnings management, there are differences in perceptions between male and female accounting students. However, the tests on misstate and cost and benefit showed no difference in perception between male and female accounting students.